Dementia enquirers: pioneering approaches to dementia research in UK. Issue 1 (2nd January 2022) - Davies, Teresa; Houston, Agnes; Gordon, Howard; McLintock, Mhari; Mitchell, Wendy; Rook, George; Shakespeare, Tom
Abstract: This paper explores the Dementia Enquirers approach to dementia research, and the 10 local projects which have been funded in the first wave of the programme. The paper is written by six people with dementia with expertise by experience, supported by a traditional academic with expertise by research. This co-production enables the voices of people with dementia to be heard, and expands the field of disability studies. The authors discuss problems with traditional academic research, and the different ways that people with dementia go about research. Two examples of research projects led by people with dementia are discussed. The paper explores difficulties people with dementia have had with formal research ethics procedures and how they propose to do things differently. In conclusion, the authors challenge mainstream dementia research to do things differently, and to understand the potential contributions of people with dementia. Points of interest: People with dementia can conduct research People with dementia understand ethics and can come to considered judgements about capacity, consent and the risk of harm. People with dementia may sometimes enjoy advantages in their ways of working Mainstream research and research governance needs to adapt, if people with dementia are to be included.